2020
DOI: 10.3390/jcm9103319
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Maintenance of Baricitinib and Tofacitinib in Real Life

Abstract: Background: Janus kinase inhibitors (JAKis) represent a new alternative to treat rheumatoid arthritis (RA). The objective of this study was to evaluate the effectiveness, tolerance profile, and maintenance of these treatments (tofacitinib and baricitinib) in real life. Methods: All patients in the rheumatology department of Amiens University Hospital treated by JAKis for RA were included from 1 October 2017 to 20 May 2020. Clinical and biological data were provided retrospectively in this observational and sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…Efficacy was observed despite the disease being active, persistent, and treatment-resistant at baseline. Despite the small sample size, the results of this study are consistent with those reported in the literature from RCTs and other realworld cohorts demonstrating an improvement in all clinimetric scores and activity indexes in both bDMARD-naïve and failure RA patients (13)(14)(15)(16)(17)(18).…”
Section: Original Papersupporting
confidence: 90%
See 1 more Smart Citation
“…Efficacy was observed despite the disease being active, persistent, and treatment-resistant at baseline. Despite the small sample size, the results of this study are consistent with those reported in the literature from RCTs and other realworld cohorts demonstrating an improvement in all clinimetric scores and activity indexes in both bDMARD-naïve and failure RA patients (13)(14)(15)(16)(17)(18).…”
Section: Original Papersupporting
confidence: 90%
“…Extensive observational research on JAKinhibs in RA is expanding, and a substantial amount of data from real-world clinical settings is now accessible. Several of these data are limited to a 12-month follow-up period (13)(14)(15)(16)(17)(18). Consequently, the primary objectives of the present study were to assess the efficacy, as measured by DAS-28 and SDAI, and safety of tofacitinib and baricitinib during a of follow-up up to 24 months in patients with RA treated in a real-world setting in Southern Italy.…”
mentioning
confidence: 99%
“…Below is a comprehensive descriptive review of the literature regarding RWE for baricitinib that has been reported to date; data were sourced from registries, monocentric and multicentric clinical practice studies, administrative or insurance claim databases, or prospective observational studies. At the time of writing, 41 published sources for RWE of baricitinib in the treatment of RA were identified [ 29 , 33 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ].…”
Section: Baricitinib In Real-world Settingsmentioning
confidence: 99%
“…Supplementary Table S1 summarises available baseline characteristics of baricitinib-treated patients in real-world settings [ 29 , 33 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. The typical patient in the various RWE sources is aged about 60 years (which is older than the mean age of patients in baricitinib RCTs).…”
Section: Baricitinib In Real-world Settingsmentioning
confidence: 99%
See 1 more Smart Citation